(untitled) (Marketing Journal, 2025)
This article provides a comprehensive analysis of the economic and social development indicators of five major regions of the world — Asia, Eurasia, Africa, North America, and South America. The study is based on key indicators such as gross domestic product, unemployment rate, and life expectancy, allowing a scientific assessment of development disparities between regions. The results demonstrate that regional differences are influenced by economic structure, labor market stability, human capital levels, and the state of healthcare systems. The article proposes practical solutions to reduce these disparities, including economic modernization, employment policy optimization, social infrastructure development, and investment in human capital. This study provides a scientific basis for developing global development strategies and enhances understanding of regional inequalities.